Dynamics of protectionism and free trade measures in the competitive confrontation between the United States and China - T. V. KOLESNIKOVA; I. M. STEPNOV (Сравнительная политика, 2023)
The article examines the reconciliation mechanism of protectionist and liberalization components in the economic policy of the United States and China. Under tightening economic competition, the U.S. and China are implementing a set of measures to support national economies, aimed both at protecting the industries which are crucial for the development of the states, and at ensuring markets for the goods produced in the country. These observations have led to the hypothesis that the set of protectionist and liberalization tools in the economic policy of countries is combined and varied to ensure economic security and international competitiveness of national economies. Based on the analysis of indicators measuring the openness of the US and PRC economies as well as a number of examples of government intervention in the economy, the authors detect the trend towards the strengthening of protectionism in the economic policy of the states since 2008. Taking into consideration the research on the participation of both countries in globalization and integration projects, the authors determine the protectionist instruments implemented by China and the USA to improve the economic growth and competitive advantage of their economies. In particular, government subsidies, fiscal tools, administrative barriers, as well as tariff measures affecting the foreign trade of the countries under study have been identified. On the basis of the comparative analysis of certain indicators measuring the manifestation of protectionist and liberalization components in the economic policy of the United States and China, the authors highlight common and different trends in combining protectionism and free trade. The synthesis of findings has led to the conclusion about the complementarity and interdependence of the tools used in the economic policy of the states aimed at increasing the competitive advantages of national economies.